Release of siRNA from Liposomes Induced by Curcumin - Kazuyo Fujita; Yoshie Hiramatsu; Hideki Minematsu; Masaharu Somiya; Shun’ichi Kuroda; Masaharu Seno; Shuji Hinuma (Journal of Nanotechnology)
Liposomes are a potential carrier of small interfering RNA (siRNA) for drug delivery systems (DDS). In this study, we searched for a molecule capable of controlling the release of siRNA from a certain type of liposomes and found that curcumin could induce the release of siRNA from the liposomes encapsulating siRNA within 30 min. However, the release of siRNA from the liposomes by curcumin showed a unique dose-response (i.e., bell-shaped curve) with a maximal induction at around 60 μg/ml of curcumin. Liposomal lipid compositions and temperatures influenced the efficiency in the release of siRNA induced by curcumin. About 10% of curcumin at a 60 μg/ml dose was incorporated into the liposomes within 30 min under our experimental conditions. Our results suggest a possibility that curcumin is useful in controlling the permeability of liposomes carrying large molecules like siRNA.